1999
DOI: 10.1097/00003246-199910000-00014
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the acute hemodynamic effects of hypertonic or colloid infusions immediately after mitral valve repair

Abstract: We conclude that in patients who have undergone mitral valve repair, postoperative infusion of hypertonic saline solutions increases left ventricular preload and left ventricular ejection fraction. The use of these hypertonic solutions may be of interest in patients with valvular cardiomyopathy. A titrated dose and a low rate of infusion may substantially improve the safety.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
10

Year Published

2004
2004
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(43 citation statements)
references
References 18 publications
1
32
0
10
Order By: Relevance
“…The cardiac effects of hypertonic saline we observed are similar to those from experiments performed in conscious individuals that demonstrated positive inotropic effects of hypertonic resuscitation (8,27,28). In contrast, studies investigating the direct cardiac effects of hypertonicity in vitro (25) and in isolated heart preparations (34), as well as in anesthetized animals and humans (5,10,13,22,38), found no or negative effects on cardiac contractility and/or output.…”
Section: Discussionsupporting
confidence: 81%
“…The cardiac effects of hypertonic saline we observed are similar to those from experiments performed in conscious individuals that demonstrated positive inotropic effects of hypertonic resuscitation (8,27,28). In contrast, studies investigating the direct cardiac effects of hypertonicity in vitro (25) and in isolated heart preparations (34), as well as in anesthetized animals and humans (5,10,13,22,38), found no or negative effects on cardiac contractility and/or output.…”
Section: Discussionsupporting
confidence: 81%
“…With the combination of a macromolecule and hypertonic NaCl, molecules remain a longer time in the intravascular space, increasing colloid osmotic pressure and plasma volume. Fluid is absorved from the interstitial intracellular space allowing for a more lasting restoration of blood volume 6,14 . This study showed short-term results of volume replacement using two different solutions in hypovolemia.…”
Section: Discussionmentioning
confidence: 99%
“…However, the cost of these solutions is high and there is a potential risk of allergic reactions and blood dyscrasia 2 . The use of small-volume hypertonic solutions for ressuscitation has proved to be an interesting alternative in experimental models of hemorrhagic shock 6 . Pioneer studies conducted in Brazil in the eighties have revealed that the infusion of small volumes of 7.5% NaCl solution produces rapid restoration of hemodynamic parameters and thus less demand for blood transfusions 7 .…”
Section: Introductionmentioning
confidence: 99%
“…Инфузия 250 мл ГР (в течение 15 мин) c целью коррек ции гиповолемии у пациентов после операций протезирования митрального клапана приводила к увеличению преднагрузки и фракции выброса ЛЖ [28]. В связи с этим использование ГР может представлять интерес у пациентов с низкими сократи тельными резервами миокарда, что, однако, требует коррекции дозировки и скорости введения препарата.…”
Section: о б з о р ыunclassified
“…Однако авторы наблюдали значимый прирост САД после инфузии ГР у боль шинства своих пациентов по сравнению с контрольной груп пой. У данных пациентов также отмечался более высокий прирост в ЦВД после инфузии ГР [28]. Феномен гипотонии основывается на периферической вазодилатации, которая объясняется рядом исследователей повышением плазменной осмолярности как с измененной, так и неизмененной концен трацией плазменного Na + [20,26,30].…”
Section: о б з о р ыunclassified